Religious Education in a Multicultural Society - Ziebertz, Hans-Georg (International journal of education and religion, 2000)
This paper begins with a presentation of three concepts of pluralism found in the works of Francois Lyotard, Jürgen Habermas and Charles Taylor respectively. These concepts are compared and evaluated and their implications for religious education in a multicultural society are developed. On the basis of Taylor's “process of encounter” three strategies for religious education are proposed: adopt new theologies of dialogue; prove its dialogical character by turning productively to the world of the pupils, and include a relativizing self-examination in the treatment of the Christian religion.